Trafficking in human beings: phenomenon and counter-measures - Di Nicola, Andrea (Henry Stewart Talks, 2008)
Trafficking in human beings (THB), Estimates on THB, THB as a form of transnational organized crime (causes, organized criminals involved, organization of trafficking, victims), National and international counter-measure against THB, Effective investigation and prosecution of THB
Archived at 2022/04/03